Red blood cell alloimmunization in transfused patients with bone marrow failure syndromes. Issue 6 (15th April 2016) - Cohen, Devin; Hartung, Helge; Evans, Perry; Friedman, David F.; Chou, Stella T.
Abstract : BACKGROUND: Red blood cell (RBC) alloimmunization is a concern for patients who receive multiple or chronic transfusions. Alloimmunization prevalence in transfused patients with bone marrow failure syndrome (BMFS) is unknown. This study aimed to determine physician practice for RBC antigen matching, immunization rates, and antibody specificities in patients with BMFS. STUDY DESIGN AND METHODS: The clinical records of all patients with BMFS seen at the Children's Hospital of Philadelphia between 2001 and 2015 were reviewed. Immunization rate was determined per 100 units transfused. RESULTS: ABO/D, C, E, and K (CEK) RBC matching was requested for 21.8% of patients. A total of 3782 RBC units were transfused to 87 patients, of which 2551 (67.5%) were CEK matched and 1231 (32.5%) were ABO/D only matched. The majority of units transfused to patients on a chronic transfusion regimen were CEK matched (89.6% of 2728 units). No anti‐C, ‐E, or ‐K antibodies formed in any patient during the 14‐year study period. Two alloantibodies and two autoantibodies formed, resulting in a rate of 0.05 alloantibodies and 0.05 autoantibodies per 100 units transfused. The prevalence of alloimmunization was 2.3%. CONCLUSION: The rate and prevalence of RBC alloimmunization were low in patients with BMFS. CEK matching avoided alloimmunization to these antigens in chronically transfused patients.